2022
DOI: 10.1111/gcb.16528
|View full text |Cite
|
Sign up to set email alerts
|

Opposing seasonal temperature dependencies of CO2 and CH4 emissions from wetlands

Abstract: Wetlands are critically important to global climate change because of their role in modulating the release of atmospheric greenhouse gases (GHGs) carbon dioxide (CO2) and methane (CH4). Temperature plays a crucial role in wetland GHG emissions, while the general pattern for seasonal temperature dependencies of wetland CO2 and CH4 emissions is poorly understood. Here we show opposite seasonal temperature dependencies of CO2 and CH4 emissions by using 36,663 daily observations of simultaneous measurements of eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Also, in the absence of data, E m was estimated using larger systems, such as lakes and reservoirs, as described in Malerba et al This approach is likely conservative for agricultural ponds. Freshwater systems of comparable sizes to agricultural ponds often record values around 1 eV, , whereas larger freshwater systems have lower values around 0.4–0.6. , Increasing the temperature sensitivity of our model would increase the total emissions. For example, increasing E m from 0.4 to 1 eV would increase our predicted methane emissions from agricultural ponds by 44% (from 41 to 59 kt CH 4 year –1 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Also, in the absence of data, E m was estimated using larger systems, such as lakes and reservoirs, as described in Malerba et al This approach is likely conservative for agricultural ponds. Freshwater systems of comparable sizes to agricultural ponds often record values around 1 eV, , whereas larger freshwater systems have lower values around 0.4–0.6. , Increasing the temperature sensitivity of our model would increase the total emissions. For example, increasing E m from 0.4 to 1 eV would increase our predicted methane emissions from agricultural ponds by 44% (from 41 to 59 kt CH 4 year –1 ).…”
Section: Discussionmentioning
confidence: 92%
“…Freshwater systems of comparable sizes to agricultural ponds often record values around 1 eV, 33 , 34 whereas larger freshwater systems have lower values around 0.4–0.6. 35 , 36 Increasing the temperature sensitivity of our model would increase the total emissions. For example, increasing E m from 0.4 to 1 eV would increase our predicted methane emissions from agricultural ponds by 44% (from 41 to 59 kt CH 4 year –1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the average daytime pCO 2 was 707 ± 642 µatm (n = 44), which was significantly elevated compared to typical atmospheric CO 2 levels (i.e., 380-420 µatm; [17,18,53]). This observation indicated that the biological productivity at a depth of 1.0 m exceeded the dissolution of water CO 2 , with the potential for CO 2 to be released into the atmosphere [10,54]. Thus, to some extent, it can be considered that this lake becomes a 'source' of CO 2 during the day.…”
Section: Changes In the Pco 2 Contribution To The Source-sink Interch...mentioning
confidence: 96%